Preparation method of high-performance flow modifier
By modifying carbon nanotubes and silicon oxide-coated carbon nanotubes in the fused ring aromatic hydrocarbon material, and combining polymer grafting technology, a high-performance flow modifier was prepared, which solved the problem of poor fluidity of the fused ring aromatic hydrocarbon material, and achieved the effect of improving fluidity and expanding application fields.
Patent Information
- Application Number
- CN202411833093.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
The poor fluidity of fused ring aromatic hydrocarbon materials at room temperature and low temperatures limits the added value of their application fields and products.
A high-performance flow modifier is used to prepare a high-performance flow modifier. The carboxylated carbon nanotubes and silicon oxide coated carbon nanotube materials are modified, combined with polymer grafting technology, and a modifier with good interfacial performance is formed, reducing the viscosity of the fused-ring aromatic hydrocarbon material and improving fluidity.
It effectively improves the fluidity of the fused-ring aromatic hydrocarbon materials, reduces their viscosity, expands their application areas, and increases the added value of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of condensed ring aromatic hydrocarbon materials, and in particular to a method for preparing a high-performance flow modifier. Background Art
[0002] Condensed aromatic materials refer to materials with two or more single aromatic rings or fused aromatic rings, in which the rings in the molecules share a pair of carbon atoms, usually in a linear, angular or clustered arrangement. The delocalized π electrons in condensed aromatic materials give them excellent charge transfer capabilities, and the CC bond energy is relatively large and not easy to break, and they have good thermal stability. The highly rigid planar structure of the benzene ring in condensed aromatic materials gives them excellent mechanical properties, as well as excellent electrical, thermal, mechanical, optical and other excellent properties, and have a wide range of applications.
[0003] Polycyclic aromatic hydrocarbons are widely used as plasticizers for rubber. Plasticizers are substances that can increase the plasticity and softness of polymer materials. In the processing of rubber, adding an appropriate amount of plasticizer can make the rubber softer and easier to process and shape. The addition of polycyclic aromatic hydrocarbons can improve the softness, processability and durability of the product, reduce costs and improve production efficiency. However, polycyclic aromatic hydrocarbons have the following problems when used as plasticizers: high density and poor fluidity at room temperature. Therefore, how to improve the fluidity of polycyclic aromatic hydrocarbons becomes the key. Summary of the invention
[0004] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing a high-performance flow modifier is provided. The flow modifier prepared by the method can effectively improve the fluidity of polycyclic aromatic hydrocarbon materials at room temperature and low temperature, greatly expand the application field of polycyclic aromatic hydrocarbon materials, and improve the added value of products.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A method for preparing a high-performance flow modifier comprises the following steps:
[0007] (1) mixing an ethanol dispersion of carboxylated carbon nanotubes, ammonia water, and deionized water uniformly, adding ethyl orthosilicate for hydrolysis reaction, filtering the reaction solution, washing the precipitate, and drying to obtain a silicon oxide-coated carbon nanotube material;
[0008] (2) adding the silicon oxide-coated carbon nanotube material to the silane hydrolyzate, stirring for reaction, cooling to room temperature after the reaction is completed, filtering the reaction solution, and washing the precipitate to obtain the modified silicon oxide-coated carbon nanotube material;
[0009] (3) dispersing the modified silicon oxide coated carbon nanotube material in anhydrous ethanol, adding acrylamide, AMPS, and sodium α-olefin sulfonate, adjusting the pH of the reaction system to neutral, introducing nitrogen to replace the nitrogen in the system, adding the first initiator, heating the reaction, cooling to room temperature after the reaction is completed, filtering, washing the precipitate, and drying to obtain a polymer grafted modified silicon oxide coated carbon nanotube material;
[0010] (4) adding acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl to deionized water and mixing them evenly, adding modified cellulose nanocrystals, adjusting the pH of the solution to neutral, replacing oxygen in the system with nitrogen, adding a second initiator to carry out a primary reaction, and then carrying out a secondary reaction. After the reaction is completed, cooling to room temperature, filtering the reaction solution, and drying the precipitate to obtain polymer-grafted modified cellulose nanocrystals;
[0011] (5) The polymer grafted modified silicon oxide coated carbon nanotube material and the polymer grafted modified cellulose nanocrystal are mixed and ground to obtain a high-performance flow modifier.
[0012] Preferably, in step (1), the concentration of the ethanol dispersion of the carboxylated carbon nanotubes is 0.001-0.003 g / ml, and the concentration of the ammonia water is 20-30 wt %; the volume ratio of the ethanol dispersion of the carboxylated carbon nanotubes, ammonia water, deionized water, and tetraethyl orthosilicate is (300-350):(40-50):(30-40):(20-25).
[0013] Preferably, in step (1), the temperature of the hydrolysis reaction is room temperature, and the time of the hydrolysis reaction is 2-5 hours.
[0014] Preferably, in step (2) and the preparation of modified cellulose nanocrystals, the preparation method of the silane hydrolyzate is: adding silane coupling agents KH550 and KH560 to a mixed solvent consisting of anhydrous ethanol, acetic acid and deionized water, controlling the volume ratio of silane coupling agent KH550, silane coupling agent KH560, anhydrous ethanol, acetic acid and deionized water to be (0.5-1): (0.5-1): 50: (1-2): (1-2), stirring and hydrolyzing at room temperature for 2-5 hours to obtain.
[0015] Preferably, in step (2), the ratio of the silane hydrolyzate to the silicon oxide-coated carbon nanotube material is (50-60) ml: (2-3) g, the stirring reaction temperature is 50-60° C., and the time is 2-7 h.
[0016] Preferably, in step (3), the modified silicon oxide coated carbon nanotube material is dispersed in anhydrous ethanol, and when acrylamide (AM), 2-acrylamide-2-methylpropane sulfonic acid (AMPS) and sodium α-olefin sulfonate (AOS) are added, the amount ratio of the modified silicon oxide coated carbon nanotube material to anhydrous ethanol is (3-8) g:50 ml, the molar ratio of AM, AMPS and AOS is (70-90):10:(5-20), and the total concentration of acrylamide, AMPS and sodium α-olefin sulfonate is controlled to be 20-40wt%; the first initiator is sodium sulfite, and the addition amount of the first initiator is 0.5-1% of the total monomer weight; the temperature of the temperature rise reaction is 40-50°C, and the time is 4-6h.
[0017] Preferably, in step (4), the preparation method of the modified cellulose nanocrystals is: dispersing the cellulose nanocrystals in anhydrous ethanol, then adding glacial acetic acid to adjust the pH to 3-4, then adding silane hydrolyzate, controlling the dosage ratio of cellulose nanocrystals to silane hydrolyzate to (3-6) g: (50-60) ml, and stirring the reaction at 40-50° C. for 3-5 h to obtain the modified cellulose nanocrystals.
[0018] Preferably, in step (4), the molar ratio of AM, AA, nonylphenol ethoxylate (NP), and 4-vinylbiphenyl (VB) is (70-75): (20-25): (1-2): (1-2); and the added amount of the modified cellulose nanocrystals is 5-7% of the total monomer mass.
[0019] Preferably, in step (4), the concentration of the hydrogen peroxide is 30wt%; the second initiator is a mixture of ferrous sulfate heptahydrate, hydrogen peroxide and 2,2'-azo(2-methylpropylamidine) dihydrochloride (V50), and the mass ratio of ferrous sulfate heptahydrate, hydrogen peroxide and V50 is 1:(3-4):5; the amount of the second initiator added is 5-6% of the total monomer mass; and / or the primary reaction is 0-10°C and the time is 5-7h; the temperature of the secondary reaction is 50-60°C and the time is 1-3h.
[0020] Preferably, in step (5), the mass ratio of the polymer grafted modified silicon oxide coated carbon nanotube material to the polymer grafted modified cellulose nanocrystals is (1-5):1.
[0021] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0022] 1. The present invention provides a method for preparing a high-performance flow modifier. The flow modifier prepared by the method is simple to prepare, has good dispersibility, has good interface properties, can effectively react with condensed aromatic hydrocarbon materials, reduce the viscosity of condensed aromatic hydrocarbons, and improve the fluidity of condensed aromatic hydrocarbon materials.
[0023] 2. The high-performance flow modifier of the present invention includes polymer-grafted modified silicon oxide coated carbon nanotubes; nano silicon oxide and carbon nanotubes both have a large specific surface area and can form physical adsorption or chemical adsorption with condensed aromatic hydrocarbon materials, thereby reducing the interaction force between molecules of condensed aromatic hydrocarbon materials, thereby reducing their viscosity and improving the fluidity of condensed aromatic hydrocarbon materials. In order to improve the interfacial properties of nano silicon oxide, carbon nanotubes and condensed aromatic hydrocarbon materials, the present invention first prepares silicon oxide coated carbon nanotube materials, and silicon oxide is uniformly dispersed on the surface of carbon nanotubes to form a coating layer, which preliminarily improves the dispersibility of silicon oxide and carbon nanotubes. In addition, the present invention uses KH550 and KH560 to modify silicon oxide coated carbon nanotubes, which is convenient for subsequent grafting of polymers. During the grafting modification, the present invention uses acrylamide, AMPS and sodium α-olefin sulfonate as polymer monomers, and grafts and modifies the surface of the silicon oxide-coated carbon nanotubes to form a ternary polymer layer. The prepared polymer grafted modified silicon oxide-coated carbon nanotubes have good compatibility with condensed aromatic hydrocarbon materials, and the ternary polymer layer has polar groups such as amide groups and sulfonic acid groups, and also contains a certain amount of hydrophobic surface active groups, has the advantages of good interfacial activity, strong emulsification, etc. After being mixed with the condensed aromatic hydrocarbon materials, it can form bonds with the condensed aromatic hydrocarbon molecules, weaken the interaction force between the condensed aromatic hydrocarbon molecules, and thus reduce the viscosity of the condensed aromatic hydrocarbon materials.
[0024] 3. The high-performance flow modifier prepared by the present invention also includes polymer grafted modified cellulose nanocrystals. The cellulose nanocrystals have a certain adsorption property, which can reduce the mutual entanglement of condensed aromatic hydrocarbon molecular chains, thereby achieving the purpose of reducing viscosity and improving the fluidity of condensed aromatic hydrocarbon materials. The present invention also uses AM, AA, NP, and VB as monomers to coat the surface of the modified cellulose nanocrystals with a polymer layer, which improves the dispersibility of the cellulose nanocrystals on the one hand, and the polymer layer on the surface of the cellulose nanocrystals has good interfacial activity, which can effectively promote the emulsification of condensed aromatic hydrocarbon materials, thereby improving the fluidity of condensed aromatic hydrocarbon materials. DETAILED DESCRIPTION
[0025] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0026] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0027] In the following examples and comparative examples, the carboxylated carbon nanotubes are black powders with a purity of >95%, a carboxyl content of 0.49 wt%, an outer diameter of >50 nm, an inner diameter of 5-15 nm, a length of 0.5-2 μm, and a specific surface area of >40 m 2 / g, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; cellulose nanocrystals were purchased from Nanjing Tianlu Nanotechnology Co., Ltd.; other raw materials were conventional commercial products unless otherwise specified, and the conditions were conventional conditions in the field unless otherwise specified.
[0028] Example 1
[0029] A method for preparing a high-performance flow modifier comprises the following steps:
[0030] (1) 330 ml of 0.001 g / ml ethanol dispersion of carboxylated carbon nanotubes, 40 ml of 25 wt% ammonia water, and 305 ml of deionized water were mixed evenly, 21 ml of ethyl orthosilicate was added, and hydrolysis reaction was carried out at room temperature for 3 h. The reaction solution was filtered, the precipitate was washed and dried to obtain a silicon oxide-coated carbon nanotube material;
[0031] (2) adding 0.5 ml of silane coupling agent KH550 and 0.5 ml of KH560 to a mixed solvent consisting of 50 ml of anhydrous ethanol, 1 ml of acetic acid and 1 ml of deionized water, stirring and hydrolyzing at room temperature for 2 h to obtain a silane hydrolyzate;
[0032] (3) Mixing 2.5 g of silicon oxide-coated carbon nanotube material and 50 ml of the silane hydrolyzate in step (2), stirring and reacting at 55° C. for 5 h, cooling to room temperature after the reaction, filtering the reaction solution, and washing the precipitate to obtain a modified silicon oxide-coated carbon nanotube material;
[0033] (4) Disperse 4 g of modified silicon oxide carbon nanotube material in 50 ml of anhydrous ethanol, add acrylamide, AMPS, and sodium α-olefin sulfonate (the molar ratio of the three is 78:10:13, and the concentration of the total monomer in the solution is controlled to be 30 wt%), adjust the pH of the reaction system to neutral, introduce nitrogen to replace the nitrogen in the system, add sodium sulfite (the amount of sodium sulfite added is 0.5% of the total monomer weight), heat to 45°C, react for 5 h, cool to room temperature after the reaction is completed, filter, wash the precipitate and dry it to obtain a polymer grafted modified silicon oxide coated carbon nanotube material;
[0034] (5) dispersing 5 g of cellulose nanocrystals in 50 ml of anhydrous ethanol, then adding glacial acetic acid to adjust the solution pH to 4, then adding 50 ml of the silane hydrolyzate of step (2), stirring and reacting at 40° C. for 4 h to obtain modified cellulose nanocrystals;
[0035] (6) Add acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl (the molar ratio of acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl is 72:20:1:1) to 80 ml of deionized water and mix well, then add 5 g of modified cellulose nanocrystals (the amount of cellulose nanocrystals added is 5% of the total monomer mass), then adjust the pH of the solution to neutral, replace the oxygen in the system with nitrogen, add a second initiator (ferrous sulfate heptahydrate, 30 wt% hydrogen peroxide, and V50 in a mass ratio of 1:3.5:5, and the amount of the second initiator added is 5% of the total monomer mass), cool to 3°C and react for 5 h, then heat to 55°C and react for 2 h, cool to room temperature after the reaction is completed, filter the reaction solution, and dry the precipitate to obtain polymer-grafted modified cellulose nanocrystals;
[0036] (7) The polymer grafted modified silicon oxide coated carbon nanotube material and the polymer grafted modified cellulose nanocrystal are mixed and ground in a mass ratio of 1:1 to obtain a high performance flow modifier.
[0037] Example 2
[0038] A method for preparing a high-performance flow modifier comprises the following steps:
[0039] (1) 330 ml of 0.0015 g / ml ethanol dispersion of carboxylated carbon nanotubes, 50 ml of 25 wt% ammonia water, and 35 ml of deionized water were mixed evenly, 22 ml of ethyl orthosilicate was added, and hydrolysis reaction was carried out at room temperature for 4 h. The reaction solution was filtered, and the precipitate was washed and dried to obtain a silicon oxide-coated carbon nanotube material;
[0040] (2) adding 0.5 ml of silane coupling agent KH550 and 0.6 ml of KH560 to a mixed solvent consisting of 50 ml of anhydrous ethanol, 1 ml of acetic acid and 1 ml of deionized water, stirring and hydrolyzing at room temperature for 4 hours to obtain a silane hydrolyzate;
[0041] (3) 3 g of the silicon oxide-coated carbon nanotube material and 50 ml of the silane hydrolyzate in step (2) were mixed, and the mixture was stirred at 55° C. for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was filtered, and the precipitate was washed to obtain the modified silicon oxide-coated carbon nanotube material;
[0042] (4) Disperse 6 g of modified silicon oxide carbon nanotube material in 50 ml of anhydrous ethanol, add acrylamide, AMPS, and sodium α-olefin sulfonate (the molar ratio of the three is 77:10:15, and the concentration of the total monomer in the solution is controlled to be 30 wt%), adjust the pH of the reaction system to neutral, introduce nitrogen to replace the nitrogen in the system, add sodium sulfite (the amount of sodium sulfite added is 0.8% of the total monomer weight), heat to 45°C, react for 4 hours, cool to room temperature after the reaction is completed, filter, wash the precipitate and dry it to obtain a polymer grafted modified silicon oxide coated carbon nanotube material;
[0043] (5) dispersing 6 g of cellulose nanocrystals in 50 ml of anhydrous ethanol, then adding glacial acetic acid to adjust the solution pH to 4, then adding 55 ml of the silane hydrolyzate of step (2), stirring and reacting at 50° C. for 3.5 h to obtain modified cellulose nanocrystals;
[0044] (6) Add acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl (the molar ratio of acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl is 72:22:1:1.5) to 80 ml of deionized water and mix well, then add 5 g of modified cellulose nanocrystals (the amount of cellulose nanocrystals added is 5.5% of the total monomer mass), then adjust the pH of the solution to neutral, replace the oxygen in the system with nitrogen, add a second initiator (ferrous sulfate heptahydrate, hydrogen peroxide with a concentration of 30 wt% and V50 in a mass ratio of 1:3.5:5, and the amount of the second initiator added is 5.5% of the total monomer mass), cool to 5°C and react for 6 hours, then heat to 50°C and react for 2 hours, cool to room temperature after the reaction is completed, filter the reaction solution, and dry the precipitate to obtain polymer-grafted modified cellulose nanocrystals;
[0045] (7) The polymer grafted modified silicon oxide coated carbon nanotube material and the polymer grafted modified cellulose nanocrystal are mixed and ground in a mass ratio of 2:1 to obtain a high performance flow modifier.
[0046] Example 3
[0047] A method for preparing a high-performance flow modifier comprises the following steps:
[0048] (1) 330 ml of 0.0025 g / ml ethanol dispersion of carboxylated carbon nanotubes, 50 ml of 25 wt% ammonia water, and 40 ml of deionized water were mixed evenly, 23 ml of ethyl orthosilicate was added, and hydrolysis reaction was carried out at room temperature for 4 h. The reaction solution was filtered, the precipitate was washed and dried to obtain a silicon oxide-coated carbon nanotube material;
[0049] (2) adding 0.5 ml of silane coupling agent KH550 and 0.5 ml of KH560 to a mixed solvent consisting of 50 ml of anhydrous ethanol, 1 ml of acetic acid and 1.5 ml of deionized water, stirring and hydrolyzing at room temperature for 4 hours to obtain a silane hydrolyzate;
[0050] (3) 2 g of the silicon oxide-coated carbon nanotube material and 55 ml of the silane hydrolyzate in step (2) were mixed, and the mixture was stirred at 55° C. for 4 h. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was filtered, and the precipitate was washed to obtain the modified silicon oxide-coated carbon nanotube material;
[0051] (4) Disperse 6 g of modified silicon oxide carbon nanotube material in 50 ml of anhydrous ethanol, add acrylamide, AMPS, and sodium α-olefin sulfonate (the molar ratio of the three is 75:10:17, and the concentration of the total monomer in the solution is controlled to be 30 wt%), adjust the pH of the reaction system to neutral, introduce nitrogen to replace the nitrogen in the system, add sodium sulfite (the amount of sodium sulfite added is 0.5% of the total monomer weight), heat to 45°C, react for 5 h, cool to room temperature after the reaction is completed, filter, wash the precipitate, and dry to obtain a polymer-grafted modified silicon oxide coated carbon nanotube material;
[0052] (5) dispersing 5 g of cellulose nanocrystals in 50 ml of anhydrous ethanol, then adding glacial acetic acid to adjust the solution pH to 4, then adding 50 ml of the silane hydrolyzate of step (2), stirring and reacting at 45 ° C for 4 h to obtain modified cellulose nanocrystals;
[0053] (6) Add acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl (the molar ratio of acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl is 73:21:1:1) to 80 ml of deionized water and mix well, then add 6 g of modified cellulose nanocrystals (the amount of cellulose nanocrystals added is 7% of the total monomer mass), then adjust the pH of the solution to neutral, replace the oxygen in the system with nitrogen, add a second initiator (ferrous sulfate heptahydrate, hydrogen peroxide with a concentration of 30 wt% and V50 in a mass ratio of 1:4:5, and the amount of the second initiator added is 6% of the total monomer mass), cool to 5°C for reaction for 5 h, then heat to 55°C for reaction for 2 h, cool to room temperature after the reaction is completed, filter the reaction solution, and dry the precipitate to obtain polymer-grafted modified cellulose nanocrystals;
[0054] (7) The polymer grafted modified silicon oxide coated carbon nanotube material and the polymer grafted modified cellulose nanocrystal are mixed and ground in a mass ratio of 3:1 to obtain a high performance flow modifier.
[0055] Example 4
[0056] A method for preparing a high-performance flow modifier comprises the following steps:
[0057] (1) 330 ml of 0.003 g / ml ethanol dispersion of carboxylated carbon nanotubes, 50 ml of 30 wt% ammonia water, and 40 ml of deionized water were mixed evenly, 25 ml of ethyl orthosilicate was added, and hydrolysis reaction was carried out at room temperature for 5 h. The reaction solution was filtered, and the precipitate was washed and dried to obtain a silicon oxide-coated carbon nanotube material;
[0058] (2) adding 1 ml of silane coupling agent KH550 and 1 ml of KH560 to a mixed solvent consisting of 50 ml of anhydrous ethanol, 1.5 ml of acetic acid and 1 ml of deionized water, stirring and hydrolyzing at room temperature for 4 hours to obtain a silane hydrolyzate;
[0059] (3) 3 g of the silicon oxide-coated carbon nanotube material and 60 ml of the silane hydrolyzate in step (2) were mixed, and the mixture was stirred at 55° C. for 6 h. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was filtered, and the precipitate was washed to obtain the modified silicon oxide-coated carbon nanotube material;
[0060] (4) Disperse 6 g of modified silicon oxide carbon nanotube material in 50 ml of anhydrous ethanol, add acrylamide, AMPS, and sodium α-olefin sulfonate (the molar ratio of the three is 74:10:18, and the concentration of the total monomer in the solution is controlled to be 35 wt%), adjust the pH of the reaction system to neutral, introduce nitrogen to replace the nitrogen in the system, add sodium sulfite (the amount of sodium sulfite added is 0.8% of the total monomer weight), heat to 45°C, react for 5 hours, cool to room temperature after the reaction is completed, filter, wash the precipitate and dry it to obtain a polymer grafted modified silicon oxide coated carbon nanotube material;
[0061] (5) dispersing 5 g of cellulose nanocrystals in 50 ml of anhydrous ethanol, then adding glacial acetic acid to adjust the solution to pH 4, then adding 60 ml of the silane hydrolyzate of step (2), stirring and reacting at 45 ° C for 4 h to obtain modified cellulose nanocrystals;
[0062] (6) Add acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl (the molar ratio of acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl is 75:24:2:2) to 80 ml of deionized water and mix well, then add 7 g of modified cellulose nanocrystals (the amount of cellulose nanocrystals added is 7% of the total monomer mass), then adjust the pH of the solution to neutral, replace the oxygen in the system with nitrogen, add a second initiator (ferrous sulfate heptahydrate, 30 wt% hydrogen peroxide, and V50 in a mass ratio of 1:4:5, and the amount of the second initiator added is 6% of the total monomer mass), cool to 5°C and react for 6 hours, then heat to 5°C and react for 3 hours, cool to room temperature after the reaction is completed, filter the reaction solution, and dry the precipitate to obtain polymer-grafted modified cellulose nanocrystals;
[0063] (7) The polymer grafted modified silicon oxide coated carbon nanotube material and the polymer grafted modified cellulose nanocrystal are mixed and ground in a mass ratio of 3:1 to obtain a high performance flow modifier.
[0064] In order to verify that the present invention has a better effect, the following is a detailed description of the comparative examples with reference to Example 4.
[0065] Comparative Example 1
[0066] Compared with Example 4, the difference is that the high-performance flow improver only includes the polymer grafted modified silicon oxide-coated carbon nanotube material, and other conditions are the same as those of Example 4.
[0067] Comparative Example 2
[0068] Compared with Example 4, the difference is that the high-performance flow improver only includes polymer-grafted modified cellulose nanocrystals, and other conditions are the same as Example 4.
[0069] Comparative Example 3
[0070] Compared with Example 4, the difference is that steps (1) to (3) are not included, and in step (4), an equal amount of carboxylated carbon nanotubes is used to replace the modified silicon oxide-coated carbon nanotube material, and other conditions are the same as those in Example 4.
[0071] Comparative Example 4
[0072] Compared with Example 4, the difference is that step (4) is not included, and other conditions are the same as Example 4.
[0073] Comparative Example 5
[0074] Compared with Example 4, the difference is that steps (1) to (3) are not included, and in step (4), modified silicon oxide-coated carbon nanotube material is not added. Other conditions are the same as those of Example 4.
[0075] Comparative Example 6
[0076] Compared with Example 4, the difference is that step (6) is not included, and other conditions are the same as Example 4.
[0077] Comparative Example 7
[0078] Compared with Example 4, the differences are: step (5) is not included, modified cellulose nanocrystals are not added in step (6), and other conditions are the same as those of Example 4.
[0079] Comparative Example 8
[0080] Compared with Example 4, the differences are: steps (1)-(3) and (5) are not included, modified silicon oxide-coated carbon nanotube material is not added in step (4), and modified cellulose nanocrystals are not added in step (6), and other conditions are the same as Example 4.
[0081] The flow improvers in the above embodiments and comparative examples were uniformly dispersed in a certain amount of xylene, 1 ml was added to 10 g of polycyclic aromatic hydrocarbon material (Bohai heavy oil BH-1, initial viscosity 4326.13 mPa·s at 50° C., and the amount of flow improver added was controlled to be 200 ppm), stirred at 60° C. for 30 min, and the viscosity of the heavy oil was measured according to the national standard "GB / T265-1988 Petroleum Product Kinematic Viscosity Determination Method and Dynamic Viscosity Calculation Method", the instrument used was SYA-265B Petroleum Product Kinematic Viscometer, and the viscosity reduction rate was calculated.
[0082] Viscosity reduction rate (%) = (η 0 -η 1 ) / η 0 ×100%;
[0083] Among them, η 0 is the original viscosity of the condensed aromatic hydrocarbon material; η 1 It is the viscosity of the condensed aromatic hydrocarbon material after being modified by a flow modifier.
[0084] The test results are shown in Table 1.
[0085] Table 1
[0086] Viscosity reduction rate (%) Example 1 98.9 Example 2 98.5 Example 3 98.9 Example 4 99.0 Comparative Example 1 79.2 Comparative Example 2 63.5 Comparative Example 3 84.4 Comparative Example 4 69.9 Comparative Example 5 80.5 Comparative Example 6 72.8 Comparative Example 7 78.7 Comparative Example 8 70.3
[0087] It can be seen from the test results in Table 1 that, relative to the comparative example, the present invention grafts a polymer layer on the surface of the silicon oxide-coated carbon nanotube material, grafts a polymer layer on the surface of the cellulose nanocrystal, and the above two materials are mixed in a certain mass ratio to form a flow modifier, which greatly reduces the viscosity of the condensed aromatic hydrocarbons and improves the fluidity of the condensed aromatic hydrocarbon materials.
[0088] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a high-performance flow modifier, characterized in that: The following steps are involved: (1) mixing an ethanol dispersion of carboxylated carbon nanotubes, ammonia water, and deionized water uniformly, adding ethyl orthosilicate for hydrolysis reaction, filtering the reaction solution, washing the precipitate, and drying to obtain a silicon oxide-coated carbon nanotube material; (2) adding the silicon oxide-coated carbon nanotube material to the silane hydrolyzate, stirring for reaction, cooling to room temperature after the reaction is completed, filtering the reaction solution, and washing the precipitate to obtain the modified silicon oxide-coated carbon nanotube material; (3) dispersing the modified silicon oxide coated carbon nanotube material in anhydrous ethanol, adding acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, and sodium α-olefin sulfonate, adjusting the pH of the reaction system to neutral, introducing nitrogen to replace the nitrogen in the system, adding the first initiator, heating the reaction, cooling to room temperature after the reaction is completed, filtering, washing the precipitate, and drying to obtain a polymer grafted modified silicon oxide coated carbon nanotube material; (4) adding acrylamide, acrylic acid, nonylphenol ethoxylate, and 4-vinyl biphenyl to deionized water and mixing them evenly, adding modified cellulose nanocrystals, adjusting the pH of the solution to neutral, replacing oxygen in the system with nitrogen, adding a second initiator to carry out a primary reaction, and then carrying out a secondary reaction. After the reaction is completed, cooling to room temperature, filtering the reaction solution, and drying the precipitate to obtain polymer-grafted modified cellulose nanocrystals; (5) The polymer grafted modified silicon oxide coated carbon nanotube material and the polymer grafted modified cellulose nanocrystal are mixed and ground to obtain a high-performance flow modifier.
2. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (1), the concentration of the ethanol dispersion of the carboxylated carbon nanotubes is 0.001-0.003 g / ml, and the concentration of the ammonia water is 20-30 wt %; the volume ratio of the ethanol dispersion of the carboxylated carbon nanotubes, ammonia water, deionized water, and tetraethyl orthosilicate is (300-350):(40-50):(30-40):(20-25).
3. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (1), the temperature of the hydrolysis reaction is room temperature, and the time of the hydrolysis reaction is 2-5 hours.
4. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (2) and the preparation of modified cellulose nanocrystals, the preparation method of the silane hydrolyzate is: adding silane coupling agents KH550 and KH560 to a mixed solvent consisting of anhydrous ethanol, acetic acid and deionized water, controlling the volume ratio of silane coupling agent KH550, silane coupling agent KH560, anhydrous ethanol, acetic acid and deionized water to (0.5-1): (0.5-1): 50: (1-2): (1-2), stirring and hydrolyzing at room temperature for 2-5 hours to obtain the product.
5. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (2), the ratio of the silane hydrolyzate to the silicon oxide-coated carbon nanotube material is (50-60) ml: (2-3) g, the stirring reaction temperature is 50-60° C., and the time is 2-7 h.
6. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (3), the modified silicon oxide coated carbon nanotube material is dispersed in anhydrous ethanol, and when acrylamide, AMPS and sodium α-olefin sulfonate are added, the molar ratio of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid and sodium α-olefin sulfonate is (70-90):10:(5-20), the amount ratio of the modified silicon oxide coated carbon nanotube material to anhydrous ethanol is (3-8) g:50 ml, and the total concentration of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid and sodium α-olefin sulfonate is controlled to be 20-40wt%; the first initiator is sodium sulfite, and the addition amount of the first initiator is 0.5-1% of the total monomer weight; the temperature of the temperature rise reaction is 40-50°C, and the time is 4-6h.
7. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (4), the preparation method of the modified cellulose nanocrystals is: dispersing the cellulose nanocrystals in anhydrous ethanol, then adding glacial acetic acid to adjust the pH to 3-4, then adding silane hydrolyzate, controlling the dosage ratio of cellulose nanocrystals to silane hydrolyzate to (3-6) g: (50-60) ml, and stirring the reaction at 40-50° C. for 3-5 hours to obtain the modified cellulose nanocrystals.
8. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (4), the molar ratio of acrylamide, acrylic acid, nonylphenol ethoxylate and 4-vinyl biphenyl is (70-75): (20-25): (1-2): (1-2); and the added amount of the modified cellulose nanocrystals is 5-7% of the total monomer mass.
9. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (4), the concentration of the hydrogen peroxide is 30wt%; the second initiator is a mixture of ferrous sulfate heptahydrate, hydrogen peroxide and 2,2'-azo (2-methylpropyl amidine) dihydrochloride, and the mass ratio of ferrous sulfate heptahydrate, hydrogen peroxide and 2,2'-azo (2-methylpropyl amidine) dihydrochloride is 1: (3-4): 5; the amount of the second initiator added is 5-6% of the total monomer mass; and / or the primary reaction is 0-10° C. and the time is 5-7h; the temperature of the secondary reaction is 50-60° C. and the time is 1-3h.
10. The method for preparing a high performance flow improver according to claim 1, characterized in that: In step (5), the mass ratio of the polymer grafted modified silicon oxide coated carbon nanotube material to the polymer grafted modified cellulose nanocrystals is (1-5):1.